PENGGUNAAN MODEL DENGAN PROGRAM CSMP UNTUK MENDUGA POTENSI HASIL PADI BERDASARKAN PENDEKATAN IKLIM, TANAH DAN TANAMAN - Woro Estiningtyas (Research Center for Biology-Indonesian Institute of Sciences, 2000)
Most of rice yield potential prediction models are focussed on optimization of two factors(i. e. soil and crop factors) than another(climate).It is probably due to significant influence of soil and crop factors thananother in rice production.In fact,the result of yield prediction taking into account soil and climate is not sufficient because climate will became limiting factor.In order to integrate climate with soil and crop factors in rice yield potential prediction,the CSMP(Continuous System Modelling Program) model is used in this research.The results of simulation shows that through climate optimization, actual rice yield production can be increased 1500-2000 kg more than actual production.Yield potential during one year can be optimised.Moreover,CSMP can give suggestion in.the efficient use of natural ressources such as nitrogen, phosphor and potassium.